Evaluation of thyroid disorders in pregnancy: prevalence and its varieties - Kaur, Harkiranjit; Padda, Maninderjit Kaur; Narayan, Ritika; Kaur, Gurpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Thyroid disorders represent one of the most common endocrine problems in pregnancy, with maternal hypothyroidism being the most frequent. Global prevalence of hypothyroidism during pregnancy varies widely, from 2.5% to 11%, and is reported to be higher in Asian countries compared to global estimates. The overall prevalence of thyroid disorder in pregnancy is estimated at up to 33.9% comprising hypothyroidism (31.6%) and hyperthyroidism (2.3%). Although hyperthyroidism is relatively uncommon, affecting only 0.1-0.4% of pregnancies, it is associated with greater maternal and fetal complications. Despite the higher prevalence of thyroid disorders in India, data on their distribution and adverse outcomes remain limited. Further research is therefore necessary to improve understanding and guide clinical practice in this population. Methods: A cross-sectional study was carried out at MGM Medical College and LSK Hospital over an 18-month period. The study population included pregnant women attending the antenatal clinic. Based on the estimated prevalence of thyroid disorders in India (33.9%), the minimum required sample size was calculated as 344 participants. Results: During the study, 344 antenatal women underwent thyroid evaluation. Of these, 112 were diagnosed with some form of thyroid disorder. The prevalence of thyroid dysfunction in pregnancy was calculated 32.56%. Conclusions: Given this high prevalence, universal thyroid function testing at the first antenatal visit is strongly recommended. Women of higher maternal age are particularly prone to developing thyroid dysfunction. The mean TSH, FT3 and FT4 values in euthyroid participants (n=232) may serve as useful reference values for this region in future studies.